2019
DOI: 10.1371/journal.pone.0225458
|View full text |Cite
|
Sign up to set email alerts
|

A simplistic approach of algal biofuels production from wastewater using a Hybrid Anaerobic Baffled Reactor and Photobioreactor (HABR-PBR) System

Abstract: The current technologies of algal biofuels production and wastewater treatment (e.g., aerobic) process are still in question, due to the significant amount of fresh water and nutrients requirements for microalgae cultivation, and negative energy balance in both processes, especially when considered in the context of developing counties around the world. In this research, a simplistic sustainable approach of algal biofuels production from wastewater was proposed using a Hybrid Anaerobic Baffled Reactor (HABR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 49 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…The reported algal biomass yield from wastewater processes can reach 0·64–14·80 g l −1 day −1 (Khalekuzzaman et al . 2019). The hydrothermal liquefaction of microalgal biomass into bio‐oil is another new route for algal fuels (Andersson et al .…”
Section: Phycoremediation Of Phenol‐polluted Petro‐industrial Effluents and Techno‐economic Sustainable Futurementioning
confidence: 99%
“…The reported algal biomass yield from wastewater processes can reach 0·64–14·80 g l −1 day −1 (Khalekuzzaman et al . 2019). The hydrothermal liquefaction of microalgal biomass into bio‐oil is another new route for algal fuels (Andersson et al .…”
Section: Phycoremediation Of Phenol‐polluted Petro‐industrial Effluents and Techno‐economic Sustainable Futurementioning
confidence: 99%
“…A newly developed microgravity-capable membrane raceway photobioreactor for Chlorella vulgaris SAG 211-12 was introduced by Helisch et al [16] for life support in space. On the other hand, Khalekuzzaman et al [17] developed a hybrid anaerobic baffled reactor and photobioreactor for a simplified method of algal biofuel production. It is important for algal biofuel production to be simple and cost-effective to make it competitive with commercially available biofuels.…”
Section: Modification Of Amino Acid Biosynthetic Pathwaymentioning
confidence: 99%
“…On the other hand, Khalekuzzaman et al [17] developed a hybrid anaerobic baffled reactor and photobioreactor for a simplified method of algal biofuel production. It is important for algal biofuel production to be simple and cost-effective to make it competitive with commercially available biofuels.…”
Section: Biofuel Production Technologymentioning
confidence: 99%
“…Figure 1 Differences in HABR and ABR reactor unit designs (Aqaneghad et al, 2017) HABR technology also uses a reactor that has several separators, but the reactor used in this technology is a combination of a suspended reactor and an attached reactor (Aqaneghad et al Aqaneghad et al, (2017), Khalekuzzaman et al, (2018) and Khalekuzzaman et al, (2019). Research conducted by Aqaneghad et al, (2017) concluded that the way HABR works is the same as ABR.…”
Section: Introductionmentioning
confidence: 99%